2020
DOI: 10.12913/22998624/122198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Trochoidal Tool Path Generation Method on the Milling Process Efficiency

Abstract: The article presents a comparison of three trochoidal paths: written by G-Code, generated using the overlays from the machine level, and generated using the CAD/CAM environment. The parameters determining the effectiveness of the process were: maximum achievable feed speed, surface roughness and waviness, cutting forces and cutting temperature when milling NC6 steel (50HRC) using a 10 mm cutter dimeter. The main measurement results include: an increase in the maximum feed speed value by almost 35% when using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…At present, the milling machine may not reach the programmed parameters to accelerate the drive lead screw because the tool path is too short [19]. The smaller the radius of the arcs forming the tool movement trajectories, the farther the actual feed speed values may be from the programmed parameters value in case of processing with a larger feed speed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the milling machine may not reach the programmed parameters to accelerate the drive lead screw because the tool path is too short [19]. The smaller the radius of the arcs forming the tool movement trajectories, the farther the actual feed speed values may be from the programmed parameters value in case of processing with a larger feed speed.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, NC tool paths are optimized along the feed direction of the tool path without the consideration of the consistency in the crossing direction. Through analyzing the relationship between cutting parameters and feed speed in cycloidal milling, Waszczuk [19] found that the actual feed speed of the machine tool is far away from the set feed speed in case of using the recommended parameters by the tool manufacturer. Moreover, the greater the curvature of the tool path, the farther the actual feed speed of the machine tool is far away from the set value.…”
Section: Fig 1 Tool Path Based On the Circle Model And The Trochoidal...mentioning
confidence: 99%
“…They observed that the true trochoidal path gave the best surface quality slightly followed by the circular-type trochoidal path, then the stretched path, and finally the semi-circular one. In later research, K. Waszczuk obtained different results; the circular-linear path was the best of them [33]. Contrary to the formerly mentioned, walls roughness is larger than that of bottom roughness, except for the third path type.…”
Section: Fig 1 Schematic Drawing Of the Trochoidal Milling Processmentioning
confidence: 90%
“…Contrary to the formerly mentioned, walls roughness is larger than that of bottom roughness, except for the third path type. However its significance, waviness of the produced slots has been mentioned in a few articles such as [4,29,33,34] as observation and has not been investigated with the machining parameters. Wagih et al developed a new path to reduce the slot waviness and surface roughness using a linear-elliptical tool path [19].…”
Section: Fig 1 Schematic Drawing Of the Trochoidal Milling Processmentioning
confidence: 99%
“…Other researchers proved that tool path considerably affects cutting forces. 1,2,32 Specific energy, U, is being employed to evaluate the process efficiency. 6,19 It can be defined as the consumed energy, E, to remove a unit volume of work material, MRV, or the ratio between cutting power, P, to material removal rate, MRR, equation (1).…”
Section: Introductionmentioning
confidence: 99%